A Method to Assess the Performance of SAR-derived Surface Soil Moisture Products - Beale, John; Waine, Toby W.; Corstanje, Ronald; Evans, Jonathan (Cranfield University, 2021)
A Method to Assess the Performance of SAR-derived Surface Soil Moisture Products John Beale, Toby Waine, Jonathan Evans, Ronald Corstanje This study brought together existing research data obtained from a number of different sources, some of which were upon request and subject to licence restrictions. Full details of how these data may be obtained are in this document
Keywords: soil moisture contents'; 'SAR'; 'Remote sensing and sensors'; 'calibration satellite data'; 'C-band SAR'; 'Sentinel-1'; 'HYDRUS 1D'; 'Soil Physics'; 'Soil Science'